The Difficulties in Moral Education and their Surmounting - Beržanskas, Gediminas (Acta Paedagogica Vilnensia, 2007)
The article deals with problems of moral education in schools and universities. It is suggested that for a long time the main difficulty of the aim had been the lack of concise and efficacious textbook. The most widespread shortages in previous textbooks are: (1) inaccurate and inadequate definitions of the main ethical notions, e.g. good, evil, virtue, vice; (2) imperfect theoretical framework and obscurity of the first principles; (3) absence of exemplary character with its main traits and preferable orientation, and ( 4) lack of basic normative prescriptions to behaviour of person. It is asserted that the characteristic shortages of ethical doctrines can be overcome and comprehensible new doctrine should be developed. The main features of the novel ought to be: precise definitions of notions 'good' and 'virtue', design of exemplary elevatic character, new formula of ethical imperative. The novel ethical imperative directly urges: 'Act only on that maxim which always obeys to good and virtue'. It is presumed the new ethical teaching is needed for creating higher kind of society.
Keywords: moral culture; moral education; ethics; goodness; personality